Auditioning for musical theatre - Berry, Denny (Routledge, 2019)
"Auditioning for Musical Theatre demystifies the process of giving the best possible professional audition for a role in a musical. It is the result of Denny Berry's own experience, sitting "behind the audition desk" for 30 years of professional Broadway auditions, as well as teaching newcomers and coaching established actors. The book coaches performers on how to be their best selves-and avoid the pitfalls of nerves and poor preparation."--Publisher's description
Includes index
Description based on print version record
Keywords: Musicals / Auditions